2005
DOI: 10.1088/0953-8984/17/27/007
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of highly ordered Sr2FeMoO6: XPS and XES studies

Abstract: We have investigated the partial densities of states of Sr2FeMoO6 by applying soft x-ray emission spectroscopy (XES) to the Fe L, the Mo M and the O K edges. We discuss the results in the light of complementary measurements of the valence band by means of x-ray photoelectron spectroscopy (XPS) and first-principles generalized gradient approximation (GGA) and LDA +U band structure calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…An excellent fit has been obtained when the peak widths for the Mo 0 , Mo 4+ , Mo 5+ , and Mo 6+ features were set to 1.0Ϯ 0.2 eV, 2.4Ϯ 0.2 eV, 1.2Ϯ 0.2 eV, and 1.3Ϯ 0.2 eV FWHM, respectively. Although the peak widths are inherently related to the natural lifetimes of the states, the larger widths found for the Mo 4+ features could be due to the presence of close-lying many-body states or defect states as hypothesized by Kuepper et al 22 It should be noted that the Mo 3d spectrum shown in Fig. 6͑c͒ is in excellent accord with the experimental 14,22 and calculated spectra 14 of polycrystalline Sr 2 FeMoO 6 reported in the literature.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…An excellent fit has been obtained when the peak widths for the Mo 0 , Mo 4+ , Mo 5+ , and Mo 6+ features were set to 1.0Ϯ 0.2 eV, 2.4Ϯ 0.2 eV, 1.2Ϯ 0.2 eV, and 1.3Ϯ 0.2 eV FWHM, respectively. Although the peak widths are inherently related to the natural lifetimes of the states, the larger widths found for the Mo 4+ features could be due to the presence of close-lying many-body states or defect states as hypothesized by Kuepper et al 22 It should be noted that the Mo 3d spectrum shown in Fig. 6͑c͒ is in excellent accord with the experimental 14,22 and calculated spectra 14 of polycrystalline Sr 2 FeMoO 6 reported in the literature.…”
Section: Resultssupporting
confidence: 82%
“…Although the peak widths are inherently related to the natural lifetimes of the states, the larger widths found for the Mo 4+ features could be due to the presence of close-lying many-body states or defect states as hypothesized by Kuepper et al 22 It should be noted that the Mo 3d spectrum shown in Fig. 6͑c͒ is in excellent accord with the experimental 14,22 and calculated spectra 14 of polycrystalline Sr 2 FeMoO 6 reported in the literature. The depth profiles of the fitted areas for the Mo 0 , Mo 4+ , Mo 5+ , and Mo 6+ 3d 5/2 features with respect to the total area of the spectrum are shown for both as-grown and postannealed films in Fig.…”
Section: Resultssupporting
confidence: 82%
“…Rather, it is extrinsic, of tunnelling magnetoresistive (TMR) origin. Since the report of the large MR eect and high magnetic transition temperature, a number of experimental studies like NMR 13 , XES 14 , Hall measurements 15 , magnetic measurements 16 have been carried out to characterize various properties of this material. There have been also a number of theoretical studies involving both rst-principles calculations 17 −20 as well as model calculations 21 −26 .…”
mentioning
confidence: 99%
“…[1]. Some of the perovskites have a large range of applications in magnetoelectric capacitors [2,3], solar cells, solid state thermoelectric Peltier coolers [4], spin filtering tunnel junction [5,6] etc. By virtue of their enriched physics and technological applications in spintronic devices [7], the oxides of double perovskites have obtained foremost significance and thus been investigated by several researchers.…”
Section: Introductionmentioning
confidence: 99%